Pelatihan Pembuatan Sabun Antiseptik Cair untuk Meminimalisasi Penularan Covid Melalui Gerakan Cuci Tangan - Kadidae, La Ode; Kadir, Laode Abdul; Nugrawaty, Andi Laila (Vokasi Universitas Halu Oleo, 2021)
Sambuli village lies along Nambo beach of Nambo district, City of Kendari Southeast Sulawesi province. This village is mainly occupied by fishermen and farmers. Nowadays, It is every citizen’s responsibility to remind each other about the danger of Covid-19 and the importance of how to limit the spread of the disease. Considering this issue, Institute of Research and Community Service Halu Oleo University arranged a team consisting of 3 academic-staff; two of them from Chemistry study program and one from Biotechnology study program, and 3 students. All the three students were from Chemistry Department. The aims of the team sent to the village were first to educate people of Sambuli about how to minimize the spread of Covid-19 disease and second is to train people of Sambuli to make liquid antiseptic soap. The soap would be used as an economical and practical substance for hand washing. The method used in this community service included public talking (mini seminar) and demonstration. During this community service, villagers got involved actively in discussion and participating actively during demonstration. They and their leaders were equally very enthusiastic and supportive. And in turn, the villagers with the assistance of students and academic staff of Halu Oleo University eventually managed to make liquid antiseptic soap by them shelves.